Impact of inflammation on anti‐oxidative effects of vitamin E‐coated membrane dialyzer in patients on chronic hemodialysis. Issue 4 (18th March 2014) - Kirmizis, Dimitrios; Papagianni, Aikaterini; Efstratiadis, Georgios; Memmos, Dimitrios
Abstract Hemodialysis (HD) with the use of vitamin E‐coated membrane (VEM) dialyzers is shown to exert anti‐inflammatory and antioxidative effects in patients with end‐stage renal disease on HD. However, the association of baseline inflammatory status with the antioxidative effects of VEM has not been investigated thus far. Thirty‐five stable end‐stage renal disease patients treated with VEM for 6 months were enrolled in the present prospective, observational cohort study. For the previous 3 months minimum, 17 (48%) patients were dialyzed with a cellulose, eight (23%) patients with a hemophane, and 10 (29%) patients with a polysulfone 1.2 to 1.5 m2 hollow fiber dialyzer. The effects of treatment on oxidized low‐density lipoprotein (oxLDL) were stratified according to half percentiles of baseline serum logC‐reactive protein and interleukin‐6, and the association between treatment goal, arbitrarily defined as a minimum 30% decrease in baseline oxLDL, was assessed with the use of logistic regression analysis. The higher C‐reactive protein and interleukin‐6 half percentiles were independently and additively associated with a higher odds ratio for achieving treatment goal. Adjustment for baseline oxLDL, age, sex, HD duration, smoking, and body mass index did not attenuate the odds ratios, whereas the history of diabetes, as primary renal disease, significantly decreased the odds ratio for achieving treatment goal. Increased baseline C‐reactive protein and interleukin‐6 are independent, additive factors associated with the effect of VEM on oxLDL in HD patients.